Engagement of older adults in STRIDE's multifactorial fall injury prevention intervention. Issue 11 (4th August 2022) - McMahon, Siobhan K.; Greene, Erich J.; Latham, Nancy; Peduzzi, Peter; Gill, Thomas M.; Bhasin, Shalender; Reuben, David B.
Abstract: Background: Evidence‐based multifactorial fall prevention interventions in clinical practice have been less effective than expected. One plausible reason is that older adults' engagement in fall prevention care is suboptimal. Methods: This was a post‐hoc analysis of 2403 older adults' engagement in a multifactorial fall prevention intervention in the Strategies to Reduce Injuries and Develop Confidence in Elders (STRIDE) pragmatic trial. Based on the direct clinical care level of the Patient and Family Continuum of Engagement (CE) framework, three indicators of progressively interactive engagement were assessed: (1) Consultation (receiving information), (2) Involvement (prioritizing risks), and (3) Partnership (identifying prevention actions). Drop off at each step was determined as well as predictors of engagement. Results: The participants' engagement waned with increasingly interactive CE domains. Although all participants received information about their positive fall risk factors ( consultation ) and most (51%–96%) prioritized them ( involvement ), fewer participants (33%–55%) identified fall prevention actions ( partnership ) for most of their risk factors, except for strength gait or balance problems (95%). More participants (70%) identified home exercises than other actions. Finally, fall prevention actions were identified more commonly among participants who received two visits compared to one (OR = 2.33 [95% CI, 2.06–2.64]), were ≥80 years old (OR = 1.83 [95% CI, 1.51–2.23]), and had fewer fall risk factors (OR = 0.90 [95% CI, 0.83–0.99]). Conclusions: The drop‐off in participants' engagement based on the level of their interaction with clinicians suggests that future multifactorial fall prevention interventions need to be more focused on interactive patient‐clinician partnerships that help older adults increase and maintain fall prevention actions. Our analyses suggest that more frequent contact with clinicians and more monitoring of the implementation and outcomes of Fall Prevention Care Plans could potentially improve engagement and help older adults maintain fall prevention actions.